Influência do tratamento com digoxina na osteonecrose dos maxilares associada ao uso de bisfosfonatos - Lemos, José Vitor Mota (2023)
Background: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) has a pathogenesis related to increased levels of pro-inflammatory cytokines, such as interleukin-17 (IL-17), produced by the Th17 immune response mediated by RORγt. Digoxin has the ability to block RORγt and it may have advantages under the bone repair process in cases of BRONJ. Purpose: to evaluate the digoxin treatment influence on the BRONJ severity in the jaw of rats treated with zoledronic acid (ZA). Materials and Methods: 40 male Wistar rats were allocated into a negative control group (NCG) (0.1ml/kg of saline), a positive control group (PCG) (ZA, 0.20 mg/kg) and three other groups treated with ZA 0.20 mg/kg associated to digoxin 1 (DG1), 2 (DG2) or 4 (DG4) mg/kg witch was administrated by gavage every three days from the protocol beginning until the euthanasia. After three consecutive weekly ZA intravenous administrations (days 0, 7 and 14), it was performed the extraction of the lower left first molar (day 42), a ZA additional dose administration (day 49) and the euthanasia 28 days after the extraction (day 70). The jaws were removed for radiographic, histomorphometric (counting of cells and empty osteocyte gaps) and immunohistochemical (Caspase-3, c-Fos, c-Jun, FoxP3, IL-2, IL-6, IL-17, NFkB, OPG, RANK, RANK-L, TGF-β TNF-α) analysis, gums were removed for western blotting (RORy) and the femur for mechanical trials. ANOVA/Bonferroni tests were used (p<0.05, GraphPad Prism 5.0). Results: the highest dose of digoxin increased diarrhea scores (p=0.028) and its use increased the kidney and heart index (p<000.1). In the femur, ZA increased maximum load (p=0.013), leak load (p=0.011), stiffness (p=0.007), maximum tension (p=0.007) and flexural modulus (p=0.006). Digoxin has reduced the suggestive area of BRONJ (p<0.001), as well as the number of polymorphonuclear cells, mononuclear cells, non-viable osteocytes and apoptotic osteoclasts (p<0.001). The two highest doses of digoxin reduced the immunoexpression for caspase-3 positive osteocytes (p=0.021). Digoxin also reduced the immunoexpression of IL-17, TNF-α, IL-6, IL-2, FOXP3, c-Jun, NFkB (p<0.001), in addition to TGF-β (p=0.009), RANKL (p= 0.035) and OPG (p=0.034). ZA increased RORγt expression (0.799±0.107) and the highest dose of digoxin (0.567±0.093) reduced this expression (p<0.001). Conclusion: Digoxin attenuated ZA-induced OMB by reducing RORγt levels and reducing Th17-associated cytokines.